Photonics Society of Poland celebrates The International Year of Light - Woliński, Tomasz Ryszard (Photonics Letters of Poland, 2015)
<span style="font-size: 8.0pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The current issue of the Photonics Letters of Poland addresses celebration of the International Year of Light by the photonics community in Poland.